Bibliometric Mapping and Clustering of Augmented Reality in Physics Education: Trends, Gaps, and Future Directions - Widiantoro, Sharfina Adelia; Wibowo, Firmanul Catur; Budi, Esmar; Bunyamin, Muhammad Abd Hadi (Jurnal Ilmiah Pendidikan Fisika, 2026)
Augmented reality is considered to have the potential to support physics teaching by visualising abstract concepts. However, to keep pace with the rapid developments across various disciplines in this field, bibliometric analysis was conducted to map the intellectual structure, identify emerging trends, and highlight potential directions for future research. This study systematically covers publications from 2012–2025, providing a comprehensive overview of research trends in AR for physics education.  The objectives of this study are: (1) to identify publication trends and main contributing institutions; (2) to identify the most productive authors, the most influential publications, and the core journals; (3) to map the main research topics and their interrelationships; and (4) to analyse collaboration patterns between countries and authors. A total of 77 documents were retrieved from the Scopus database and analysed using descriptive bibliometric techniques and science mapping. In this study, the topics “augmented reality” and “students” emerge as the most central nodes, indicating the primary focus of the research and serving as links between research clusters. Thematic analysis also indicates that niche themes, such as “learning outcomes” and “teaching”, are not yet widely connected to motor themes, highlighting potential directions for future research, including exploring integration between these two groups and investigating more integrated approaches in technology-enhanced physics learning. These findings can provide guidance for researchers in physics education and suggest areas for further studies to explore more integrated approaches in AR-supported learning, contributing to the ongoing development of physics education research.